Penerapan Zoho Untuk Sistem Presensi Pengajar Ekstrakurikuler Di SDIT Insan Mandiri Kalisari - Asqia, Misna; Afiah, Afra (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
Extra-curricular activities are additional activities facilitated by the school to develop the interest and the talents of the pupils. In these activities, teachers are entitled to special incentives for teaching outside regular working hours. Therefore, there is a need for a presence system that makes it easy for the entire user to make presence. Zoho Forms and Zoho Sheets were chosen as platforms to implement this presence. In order for the system to be used optimally, observations must be made of all the parties who will use the system by conducting interview. After obtaining the needs of the user, the system is designed and implemented using Zoho Forms that are integrated with Zoho Sheets for ease to facilitate incentive calculation. Thes system was tested using the black box testing methods carried out by the author by determining the test scenario with the results showing that five of the seven scenarios, or about 71% of the features, were specified according to the needs. As for the open beta testing conducted by the user, using online questionnaires as a data collection method. The test result were processed using a Guttman scale that resulted in 91% user extracurricular teachers, 100% user responsible extracurricular, and 100% user deputy head of school field of appretianceship agreed that the system created was already in line with the needs of the user. This research is expected to make it easier for all parties to use the presence system.